Broadband RF Interferometric Mapping and Polarization (BIMAP) Observations of Lightning Discharges: Revealing New Physics Insights Into Breakdown Processes. Issue 18 (26th September 2018) - Shao, Xuan‐Min; Ho, Cheng; Caffrey, Michael; Graham, Paul; Haynes, Brian; Bowers, Gregory; Blaine, William; Dingus, Brenda; Smith, David; Rassoul, Hamid
Abstract: Broadband radio frequency (RF) interferometry was first introduced in 1996 for lightning studies. The technique has since been improved significantly and has been increasingly widely used in the lightning community. In addition to the interferometry, we now introduce a broadband polarization capability that simultaneously measures the full polarization state of the corresponding RF sources. Polarization observation provides another level of understanding of the discharge processes. In this paper, we describe the new system and present example observations with such a system. Initial observations of impulsive lightning RF pulses, a K‐event leader, and the initiating process for an intracloud flash are presented. The impulsive pulses were often linearly polarized and are consistent with conventional breakdown processes, whereas some occasional pulses were elliptically polarized and are likely related to relativistic breakdown processes. The K‐event was detected polarized along a section of its channel, and the orientation of the polarization was mostly orthogonal to the channel, apparently due to the preceding charge deposition along the channel. The intracloud flash in this paper was initiated with downward fast positive streamers, and the corresponding signals were linearly polarized, consistent with conventional breakdown processes. The orientations of the polarization were nearly uniformly aligned with the propagation direction of the streamers, indicating a near uniform electric field in the region of the initiating streamers. Finally, an observation of a cosmic‐ray shower is presented. Key Points: A new broadband radio frequency interferometry and polarization system for lightning study is introduced Impulsive pulses are observed often linearly polarized while occasional pulses elliptically polarized, related to conventional/relativistic breakdowns Lightning is initiated with fast positive streamers that show no evidence of relativistic process